SOME PROBLEMS OF LEGAL REGULATION OF BARTER AND DONATION AGREEMENTS AS THE INDIVIDUAL KINDS OF CONTRACTS FOR PROPERTY TRANSFER - Indira Karzhaubayevna, Елеусизова; Dana Manarovna, Калкенова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
The article discusses some of the issues of legal regulation and donations agreements under the laws of the Republic of Kazakhstan and makes appropriate recommendations to improve the rules of civil law in this area.